EFFORTS TO IMPROVE MATHEMATICAL CREATIVE THINKING OF SMK STUDENTS IN 2023 BY USING A PROBLEM-BASED LEARNING MODEL ASSISTED BY QUIZIZZ - Hendriana, Benny; Akbar, Rayhan Muhammad (FKIP Universitas Muhammadiyah Tangerang, 2024)
This research is classroom action research (PTK) which aims to increase efforts in students' creative thinking abilities through the application of the Problem Based Learning (PBL) model in class X-DKV SMK MALAKA in the 2022/2023 Academic Year. The subjects of this research were 37 students from class The results of this research are: a) Students who have very creative criteria; b) Students who have creative criteria; c) Students who have the criteria to be creative enough; d) Students who have less creative criteria; e) Students who have criteria for not being creative. The results of the initial test show that students have criteria for not being creative with an average score of 57.16. After receiving lessons given through the Problem Based Learning learning model, students showed increased creative thinking abilities. This is shown by comparing Cycle I with Cycle II, or by comparing the initial stage of Student Ability Tests. These two comparisons show that, no student can achieve the goal at their current level of creative thinking ability. In cycle I, the overall student success rate was 49% (18 of the total students), with an average score of 63.51. In cycle II, the percentage of successful students increased to 81% (30 of the total students), with an average score of 86.89.